Practical Considerations for the Assessment and Treatment of ADHD in Children with Epilepsy - Tangen, Rachel Burmeister; Diekroger, Elizabeth Ann (Journal of Pediatric Epilepsy, 2018)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent psychiatric comorbidities in children with epilepsy, but it is under diagnosed and under treated which can impact the quality of life. Knowledge regarding ADHD characteristics, epilepsy-related risk factors, and associations with specific types of epilepsy provide a base for assessment. Epilepsy-related variables have not consistently predicted ADHD status, so screening and assessment for ADHD in children with epilepsy should be systematic and broad. Different assessment tools and techniques can be helpful including rating scales, diagnostic interviews, and neuropsychological testing. Treatment of ADHD with methylphenidate has been found to be safe and effective including in populations with uncontrolled seizures and coexisting intellectual disability. There are limited data on other medication and behavioral treatments. To improve assessment, diagnosis and treatment, medical provider knowledge, and practices, as well as family barriers to behavioral health should be targeted.
Keywords: attention deficit hyperactivity disorder; pediatric epilepsy; behavioral aspects of childhood epilepsy